Antibodies as anti-virals - Burton, Dennis (Henry Stewart Talks, 2007)
Anti-viral activities of antibody in vitro, Neutralization, Mechanisms of neutralization, Other activities against free viruses, Activities against infected cells, Antibody mediated enhancement, Anti-viral activities of antibodies in vivo, Protection, Antibodies in therapy of viral infection, Viral strategies for avoiding antibody responses
Archived at 2021/02/25